Grammatical competence of ESL teachers - Mafisa, Palesa J.; van der Walt, Johann L. (Per Linguam : A Journal of Language Learning, 2002)
The aim of this article is to report on a study investigating the grammatical competence of English Second Language teachers in secondary schools. This study came about as a result of the widespread concern that these teachers may not always be competent enough in English. We determined the teachers’ familiarity with standard English grammar as well as their acceptance of Black South African English features. The findings indicate that teachers had problems with the grammatical structures tested and accepted some Black South African English grammatical features as correct usage.